AKTIVITAS ENZIM KATEPSIN DAN KOLAGENASE PADA KULIT IKAN BANDENG (Chanos chanos, Forskal) SELAMA PERIODE KEMUNDURAN MUTU - TATI NURHAYATI; ELLA SALAMAH; MOHAMMAD IRFAN; RONI NUGRAHA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2010)
Fish skin is one of many parts from fish that can be utillized beside the muscle. Proteolytic enzymes like cathepsin and collagenase are known as one of the factors that influence in fish skin quality deterotiation after death. The research purposes were to determine post mortem phase, quality deterioration pattern, cathepsin and collagenase activity, and its correlation to the parameters of milkfish freshness. The observations were done on fasted and fed fish before harvested at room and chilling temperature storage. The highest chatepsin and collagenase activity i.e. 7800-1429 U/ml and 0,0667-0,0792 U/ml respectively, were found in fish during the post-rigor phase. Simple linear correlation analysis showed that chatepsin and collagenase activity have a very close linear relationship (r 0.7) with fish freshness quality parameters during the process of quality deterioration from pre rigor until post rigor phase.